Stefan Uroš II Milutin – działalność fundacyjna serbskiego króla - Piórecka, Agnieszka (Vox Patrum, 2016)
Biographer of Stefan Uroš II Milutin, Archbishop Danilo II, states in his book that about fifteen churches and monastery buildings, were erected under the auspices of the Serbian king. They were created in Serbia, Constantinople, Thessalonica, Athos, Jerusalem and Sinai. Similarly, as byzantine Emperor, the Serbian king not always founded new objects. Occasionally, as it was in the case of the church in Staro Nagoričino, he only resurrected run-down buildings. Probably, as the result of this activity there is such an architectural variety of his foundations. Since the moment of his marriage to the daughter of the Byzantine Emperor, Andronikos II Palaiologos, Simonis in 1299, started the specific spread of byzantine domination in Serbia, also in architecture. Erecting buildings in byzantine style, the king employed master builders from the area of Empire. In the case of churches in Prizren (Bogorodica Ljeviška) and in Staro Nagoričino, we can observe influence of Epirus architecture.